Coated chitosan onto gauze to efficient conditions for maintenance of the wound microenvironment - Souza, Jefferson (2017)
The aim of this work was to evaluate the thermo-physiological comfort and moisture properties of surgical cotton gauze coated with chitosan (CH). Gauze was coated with CH at mass fractions of 0.50, 0.25, 0.125, 0.10, 0.063 wt%. Results indicate that the functionalized medical gauze induces low capilarity, allowing a good degree of moisture and absorption capacity of wound exudates. This biofunctional medical gauze coated with CH0,125 wt% demonstrates to deliver an efficient coating and promote the best conditions for maintenance of the wound microenvironment.